On Gaver's parallel system supervised by a safety unit: The global recovery time. Issue 20 (18th October 2022) - Vanderperre, Edmond J.; Makhanov, Stanislav S.
Abstract: We introduce the global recovery time of Gaver's parallel system supervised by a safety unit. The entire system is attended by two heterogeneous repairmen. Our methodology is based on the theory of sectionally holomorphic functions combined with the notion of dual transforms. As an application, we consider the particular case of Coxian distributions.